Legal certainty as a requirement for the formalization of legal norms - Adaskalytsia K. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of the article is to define and disclose the basic requirements of the principle of legal certainty in the context of formalization of legal norms. Methodology. The methodology includes the analysis of scientific works and precedent practice of the European Court of Human Rights, the synthesis of scientific knowledge and the construction of well-grounded conclusions regarding the research subject. The following methods of scientific cognition were used during the research: analysis of literary sources, dogmatic, comparative legal, system method, logical reasoning. Results. The study illustrated that there are different approaches to the principle of legal certainty, which are united by the concepts of "clarity" and "comprehensibility" of legal provisions as the main requirements for the formalization of legal norms. Ensuring a high level of "clarity" and "comprehensibility" of legal provisions at the same time is impossible, because high "clarity" leads to a loss of "comprehensibility" and vice versa. Therefore, approaches to determining the minimum threshold and a reasonable balance, which depend on a specific field of law, are proposed in the study. It is also justified that the requirement of "clarity" is a priority, and the requirement of "comprehensibility" is desirable, but secondary. Originality. The research systematically examines the practice of the ECHR along with the achievements of domestic and foreign scientists in order to establish the requirements for the formalization of legal norms derived from the principle of legal certainty. Practical significance. The research results can be used to improve law-making and law-enforcement practices. The research findings can be useful for judges, lawyers, and other legal professionals. The research can be used in the educational process when teaching the theory of law and industry-specific legal disciplines.